Management and Development Website www.rumahkartini.com - Hendra Prayoga, Mardhani; Widagdo, S.Sos, M.I.Kom, M. Bayu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Kartini Community House create a website www.rumahkartini.com to provide information about the history Jepara and Kartini via online. This website began to be managed and developed to be used by the public seeking information about the history Kartini and Jepara. Destination management and development website www.rumahkartini.com is to present a variety of information about the history and culture that exists around Jepara through www.rumahkartini.com with basic journalism website is true and can be accessed by the audience. And to increase the number of visitors to the website. Total amount of news that managed is 31 news (the target of 30 articles) within one month. Capable of filling the entire content provided, with the highest number of posts about the Old Days section are 13 article, Discovery 8 article, article 6 about Event Program and Culinary 4 articles. In the process of implementation of site management www.rumahkartini.com, based on the results of the calculation of the number of visitors and success to fill in all sections are provided, the total accumulative, visitors on May 17, 2016 until June 16, 2016 reached 4,391 from the minimum target of 1,500 visitors. Average visitors per day are 141, from the minimum target of 50 visitors. There are some significant obstacles in the process of management and development website www.rumahkartini.com. There are several types of news posting schedule shift. It also jobdesc group that did not go according to the original plan.